The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1088/0954-3899/21/5/008
|View full text |Cite
|
Sign up to set email alerts
|

Limits on neutrino masses from the tritium beta spectrum

Abstract: The beta spectrum of tritium has been studied with a pi square root (13)/2-spectrometer. The source consisted of tritium in the atomic form embedded in a metal-dioxide lattice. The measured spectrum was analysed down to 14 keV. All fitting parameters used, in addition to the mass parameter mnu , could be checked by independently determined physical values. No evidence for a non-vanishing antineutrino mass or a mixed state with a heavy antineutrino admixture in the mass region from 0.010 to 4 keV/c2 was found. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
44
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 42 publications
(3 reference statements)
1
44
0
Order By: Relevance
“…3. The existing previous limits obtained by studying the 3 H beta decay by Hiddeman et al [3] and Simpson [4] are also reported in the figure for comparison. Limits of 9 3 10 23 at 1000 eV͞c 2 , 1.2 3 10 22 at 500 eV͞c 2 , 4.4 3 10 22 at 200 eV͞c 2 , and 0.116 at 100 eV͞c 2 at 95% C.L.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…3. The existing previous limits obtained by studying the 3 H beta decay by Hiddeman et al [3] and Simpson [4] are also reported in the figure for comparison. Limits of 9 3 10 23 at 1000 eV͞c 2 , 1.2 3 10 22 at 500 eV͞c 2 , 4.4 3 10 22 at 200 eV͞c 2 , and 0.116 at 100 eV͞c 2 at 95% C.L.…”
mentioning
confidence: 82%
“…1) [10,11]. The low end-point energy of the 187 Re decay (2470 6 5 eV [11]) and the good performances of the detector, especially in terms of energy resolution and detector response, allow significantly improved limits on the mixing angle of heavy mass neutrino in the mass interval between 50 and 1000 eV, which has been rarely investigated before [3,4].The calorimetric experiment measures not only the beta energy, but all the detectable energy released in the process (the electron energy and the excitation energy of the residual system) provided that the energy is fully thermalized. The measured spectrum is therefore well suited for neutrino mass investigations because it is complementary to the neutrino energy spectrum and is unaffected by the final state distribution or by secondary interactions of emitted electrons.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 as a function of sterile neutrino mass. In the same figure we also present the existing published limits [7][8][9][10][11]. at 95% confidence level.…”
mentioning
confidence: 86%